Evaluation of pulmonary tuberculosis disease burden in Shenyang, China, 2023 - Huijie Chen; Haiyan Bi; Peng Li; Zhixing Yang; Lihai Wen; Baijun Sun; Wei Sun (BMC Infectious Diseases)
Abstract Background Pulmonary tuberculosis (PTB) is one of the most serious infectious diseases worldwide and poses a great threat to people’s health. China has a vast territory with substantial regional disparities in the PTB disease burden. However, there have been no studies conducted to evaluate the PTB disease burden in Shenyang. The aim was to elucidate the magnitude, composition, and distribution of PTB disease burden in Shenyang. Methods The disability-adjusted life years (DALYs) calculated based on Global Burden of Disease (GBD) framework was used to assess the disease burden of PTB in Shenyang in 2023, and descriptive epidemiological methods were employed to elucidate the magnitude, composition, and distribution characteristics of PTB disease burden in Shenyang. Results In 2023, 4,169 PTB cases were reported in Shenyang, including 2,901 males and 1,268 females. The incidence of PTB was 45.50/105, of which 64.29/105 for males and 27.30/105 for females. The incidence among males was higher than that among females (X 2 = 688.56, p<0.001). The highest incidence was 107.00/105 in the group of the population aged 80 and above (X 2 = 1171.75, p<0.001). In 2023, 189 PTB deaths were reported in Shenyang, including 156 males and 33 females. The mortality of PTB was 2.06/105 of which 3.46/105 for males and 0.71/105 for females. The mortality among males was higher than that among females (X 2 = 83.69, p<0.001). The highest mortality was 16.04/105 in the group of the population aged 80 and above (X 2 = 285.61, p<0.001). The PTB DALYs rate was 58.25/105, of which 91.73/105 for males and 21.22/105 for females. The DALYs rate among males was higher than that among females (X 2 = 44.04, p<0.001). The highest DALYs rate was 149.86/105 in the group of the population aged 80 and above (X 2 = 305.35, p<0.001). Years of life lost (YLLs) due to PTB accounted for 71.38% of total DALYs, of which 74.33% for males and 52.89% for females. Conclusion The PTB DALYs rate in Shenyang was 58.25/105, which was lower than that in China, equivalent to 80% of the national PTB disease burden rate. The disease burden showed a characteristic of increasing with age, and the PTB DALYs rate for males was higher than that for females, being equivalent to 4 times the female rate. The predominant disease burden of PTB was attributed to YLLs, accounting for as much as 71.38%, indicating that PTB primarily results in premature mortality rather than disability. Therefore, the focus should be shifted towards early intervention to reduce transmission, especially for the aged males.